2008
DOI: 10.1073/pnas.0802066105
|View full text |Cite
|
Sign up to set email alerts
|

Tracking butterfly movements with harmonic radar reveals an effect of population age on movement distance

Abstract: We used harmonic radar to track freely flying Glanville fritillary butterfly (Melitaea cinxia) females within an area of 30 ha. Butterflies originated from large and continuous populations in China and Estonia, and from newly established or old (> 5 years) small local populations in a highly fragmented landscape in Finland. Caterpillars were raised under common garden conditions and unmated females were tested soon after eclosion. The reconstructed flight paths for 66 individuals comprised a total distance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 27 publications
9
133
0
Order By: Relevance
“…The observed variation among individuals during a single short flight bout can be expected to have significant consequences for the fitness and dispersal distances in the life time of a butterfly, during which it performs thousands of such short flight bouts (see Ovaskainen et al. 2008). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The observed variation among individuals during a single short flight bout can be expected to have significant consequences for the fitness and dispersal distances in the life time of a butterfly, during which it performs thousands of such short flight bouts (see Ovaskainen et al. 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Ovaskainen et al. (2008) showed that the longer dispersal distances at low ambient temperatures of butterflies from newly colonized populations, which consist of dispersive individuals with higher than average FMR (Hanski et al. 2002; Haag et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas birds can be ring marked or tracked via GPS or sun loggers, only the very largest and least abundant insects can be equipped with electronic tags [2,3]. While research in the area of radar entomology has been conducted over several decades and numerous interesting applications have been described [4], laser radar (light detection and ranging; lidar) systems in the optical regime have the potential of achieving a far better sensitivity and address and classify even the tiniest insects, simply because most insects are much smaller than the wavelengths of microwaves used in radars but larger than the wavelengths of light.…”
Section: Remote Optical In-situ Insect Monitoringmentioning
confidence: 99%